Editorial for Journal of Proteomics and Genomics Research - Diana M. Gilligan (Journal of Proteomics and Genomics Research, 2012)
An editorial announcing the journal’s launch sets expectations for data standards, reproducibility, and integrative omics studies with clinical relevance.